The Effect of Store Atmosphere and Social Media Marketing on Purchase Decisions on Consumers of the Damandiri Cafe - Dasmadi, Dasmadi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to determine and analyze the influence of social media and store atmosphere on purchase intention at the Damandiri cafe in Selo, Boyolali Regency. This type of research is quantitative research using a conclusive classification: data collection techniques using non-probability sampling classification and judgmental techniques. The number of samples used in this study was as many as 100 respondents who knew and had accessed the Instagram account of Damandiri café. The analysis technique uses multiple linear regression analysis with the SPSS version 25 program. The results show that social media positively and significantly affect purchase intention at Damandiri cafe in Selo, Boyolali. There is a significant influence of the store atmosphere has a positive and significant effect on the purchase intention of a Damandiri café in Selo, Boyolali. Café Damandiri is expected to be able to design outlets in such a way as to increase customer convenience with a positive store atmosphere. In addition, it is expected to consider the social media to increase consumer purchase intention. Further research can use newer variables such as convenience, promotion, or service quality.